Hyperthyroidism in non-seminomatous testicular germ cell tumors: two case reports and literature review - Favero, Diletta; Oing, Christoph; Seidel, Christoph; Rescigno, Pasquale; Catalano, Fabio; Cremante, Malvina; Rebuzzi, Sara Elena; Gatto, Federico; Rosti, Giovanni; Ferone, Diego; Fornarini, Giuseppe; Cocchiara, Francesco (Frontiers in Oncology, 2024)
Background: Human chorionic gonadotropin (hCG)-induced hyperthyroidism is a rare paraneoplastic syndrome observed in non-seminomatous testicular germ cell tumours, due to a cross-reaction between the β-subunit of hCG with the TSH receptor. The precise prevalence of this paraneoplastic phenomenon is unclear as in the majority of cases hyperthyroidism remains subclinical.Case presentation: Here we present two cases of advanced metastatic non-seminomatous testicular germ cell tumours where patients exhibited signs and symptoms of thyrotoxicosis at primary diagnosis due to excessive serum β-hCG elevation, with complete remission of symptomatology after the start of oncological treatments and no signs of relapse at the time of publication of this report. Additionally, we provide a comprehensive review of the existing literature concerning this uncommon occurrence.Conclusions: Despite being a rare event, the presence of hyperthyroidism or thyrotoxicosis without clear aetiology in a young man should lead to consider less frequent causes such as testicular tumours. Even if patients typically have mild symptoms that resolves after chemotherapy, in rare cases it can be a life-threatening condition that requires prompt recognition and specific intervention.